2006
DOI: 10.1007/s10072-006-0662-3
|View full text |Cite
|
Sign up to set email alerts
|

The Von Restorff effect in ageing and Alzheimer’s disease

Abstract: The purpose of the study was to evaluate the Von Restorff effect in normal ageing and in Alzheimer's disease (AD). A shortened paradigm was administered to three groups of subjects: young volunteers, elderly volunteers and patients with early-stage AD (MMSE>20). Each subject was presented with 25 lists of 10 words each, the target word appearing in double font size. A free recall phase followed the presentation of each list; after completion of the battery, a size recognition test was administered and subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 12 publications
4
25
2
Order By: Relevance
“…Also, similar levels of the isolation effect were shown across age groups when the distinctive item was radically different from the other items, such as digits presented in a list of words (Smith, 2011). Furthermore, reduced age differences were shown in an examination of isolation effects based on font size in which younger adults reported greater spontaneous use of elaborative semantic encoding strategies than older adults (Vitali et al, 2006) strategies that may have attenuated the intended isolation effect in younger adults.…”
mentioning
confidence: 81%
“…Also, similar levels of the isolation effect were shown across age groups when the distinctive item was radically different from the other items, such as digits presented in a list of words (Smith, 2011). Furthermore, reduced age differences were shown in an examination of isolation effects based on font size in which younger adults reported greater spontaneous use of elaborative semantic encoding strategies than older adults (Vitali et al, 2006) strategies that may have attenuated the intended isolation effect in younger adults.…”
mentioning
confidence: 81%
“…Geraci et al (2009) suggested that older adults lack the attentional control necessary for observing a strong isolation effect. Vitali et al (2006) reported an isolation effect in older adults free from cognitive impairment that was not observed in a comparison group with Alzheimer's disease. These researchers suggested that the unimpaired participants responded to stimulus novelty with increased encoding and visual-perceptual processing; however, Alzheimer's participants failed to engage in extra processing of isolated items.…”
Section: Attention and The Midlist Isolation Effectmentioning
confidence: 99%
“…In contrast, Vitali et al (2006) found no age difference in isolation effects using sequential presentation of 10 words, with the isolate twice the size of non-isolates, followed by free recall. In the control condition, all words were the same size.…”
Section: Isolation Effects In Older Adultsmentioning
confidence: 63%
“…Currently, only five studies exist where isolation effects have been compared between young and older participants (Bireta et al, 2008;Cimbalo & Brink,1982;Geraci, McDaniel, Manzano, & Roediger, 2009;Smith, 2011;Vitali et al, 2006). In these studies, isolation effects for older participants compared to young participants were the same (Geraci et al, 2009;Vitali et al, 2006), reduced (Bireta et al, 2008), or absent for older participants yet present in young participants (Cimbalo & Brink, 1982); Smith (2011) found a mixture of age differences within her study.…”
Section: Isolation Effects In Older Adultsmentioning
confidence: 79%
See 1 more Smart Citation